Determinan Analyis of Poverty in Lampung Province - Supaijo; Rahman, Taufiqur; Fasa, Muhammad Iqbal (Al-Ulum, 2024)
This study aims to analyze the influence of pure participation rates and open unemployment rates on poverty in regencies and cities in Lampung Province partially and as a whole. The data used in the study are secondary data from 5 regions in Lampung Province for the period 2018-2021. The method used is Panel Data Regression Analysis using the program Eviews10.0 to analyze the effect of pure participation rate and open unemployment rate on poverty of Regency and City in Lampung Province. The tests used are Chow test, Hausman test, t test and F test. The results of the Chow Test show that the methodfixed effectbetter than the common effect method used in this study. The results of the Hausman Test indicate that the random effect method is better used than the fixed effect method in this study so that the model used is random effect. Data analysis shows that the Pure Participation Rate and the Open Unemployment Rate together have a positive and significant effect on Regency and City Poverty in Lampung Province. Partially, the Pure Participation Rate has a negative but insignificant effect on Poverty, and the Open Unemployment Rate has a positive but insignificant effect on Regency and City Poverty in Lampung Province.